PANDANGAN MAZHAB FIQH DALAM KES BATAL WUDUK APABILA BERSENTUH ANTARA LELAKI DAN WANITA BUKAN MAHRAM SEMASA TAWAF: SATU ANALISIS - Ab Ghani, Anisah (Jurnal Syariah, 2008)
The study discusses views of scholars of the four main Islamic jurisprudence schools, their juristic reasoning and each school’s preferred (rajih) view on the nullity of ablution as a result of skin-toskin contact between ajnabi (lawfully eligible for marriage) male and female. The study shows that the preferred view of Maliki and Hanbali Schools and the minority view within Shafie School is the most juristically sound. The view holds that skin-to-skin contact between ajnabi male and female with no inducement of sexual passion (syahwat) does not result in nullification of an ablution. In addition, the study suggests that this juristic view should carry more practical relevancy for Shafie School adherents in the context of pilgrimage (hajj), particularly in performing tawaf.